Kytsivka sands as a refuge of the rare spider species (Aranei) of Kharkiv Region (Ukraine) - Полчанінова, Н. Ю. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
A checklist of 62 spider species found at the sands near the village of Kytsivka is given. Regionally rare species comprise 29% of the local spider fauna; three of them are listed in the Red Data Book of Kharkiv Region (Yllenus vittatus, Mustelicosa dimidiata, Xysticus mongolicus), two species are new for the Region (Yllenus arenarius, Philodromus pictus). For eleven species (Aculepeira ceropegia, Haplodrassus bohemicus, Micaria lenzi, Mustelicosa dimidiata, Philodromus pictus, Pellenes nigrociliatus, Sitticus penicillatus, Yllenus arenarius, Y. vittatus, Xysticus mongolicus, X. sabulosus), it is a single known locality in northeastern Ukraine.